PSYCHOSOCIAL STRESSORS, BURNOUT AND MENTAL HEALTH PROBLEMS IN CAREGIVERS OF CHILDREN WITH CEREBRAL PALSY - Naeem, Fatima; Arif, Samia; Asghar, Ayesha; Mahmood, Zahid (Journal of Postgraduate Medical Institute, 2018)
Objective: To explore the relationship between psychosocial stressors, burnout and mental mealth problems in caregivers of children with cerebral palsy. Methodology: Cross sectional research design was used in the current research. The sample comprised of 93 mothers of children with cerebral palsy selected from 3 institutes of special education in Lahore, through purposive sampling strategy. They were given demographic proforma, psychosocial stressors scale, caregiver burnout scale and depression & anxiety stress scale (DASS-21). Results: There was positive relationship between psycosocial stressors i.e. lack of self-regulation (p <.001), lack of social support (p <.034), burnout i.e. withdrawal (p <.007), somatic problems (p <.001), reactivity (p <.012) were found to be a significant positive predictor of depression, stress and anxiety in mothers of children with cerebral palsy. Conclusion: There was a positive relationship between lack of self-regulation, lack of social support, withdrawal, somatic problems, reactivity and depression, stress & anxiety in mothers of children with cerebral palsy.